Pyrolysis and oxy-fuel combustion characteristics and kinetics of petrochemical wastewater sludge using thermogravimetric analysis. (December 2015) - Chen, Jianbiao; Mu, Lin; Cai, Jingcheng; Yao, Pikai; Song, Xigeng; Yin, Hongchao; Li, Aimin
Highlights: Pyrolysis/oxy-fuel combustion of petrochemical wastewater sludge was studied by TGA. Pyrolysis in N2 proceeded in three steps, while four steps for degradation in oxy-fuel atmospheres. Combustion under oxy-fuel conditions resulted in a delay in the thermal profiles. Increasing O2 concentration could improve the combustion performance of PS. Kinetics of PS decomposed in various conditions was obtained by Coats–Redfern method. Abstract: The pyrolysis and oxy-fuel combustion characteristics of petrochemical wastewater sludge (PS) were studied in air (O2 /N2 ) and oxy-fuel (O2 /CO2 ) atmospheres using non-isothermal thermogravimetric analysis (TGA). Pyrolysis experiments showed that the weight loss profiles were almost similar up to 1050 K in both N2 and CO2 atmospheres, while further weight loss took place in CO2 atmosphere at higher temperatures due to char–CO2 gasification. Compared with 20%O2 /80%N2, the drying and devolatilization stage of PS were delayed in 20%O2 /80%CO2 due to the differences in properties of the diluting gases. In oxy-fuel combustion experiments, with O2 concentration increasing, characteristic temperatures decreased, while characteristic combustion rates and combustion performance indexes increased. Kinetic analysis of PS decomposition under various atmospheres was performed using Coats–Redfern approach. The results indicated that, with O2 concentration increasing, the activation energies of Step 1 almost kept constant, while the values of subsequent three steps increased.